A simplified and higher dynamic range version of the J(1) ... J(4) method for optical phase measurements - Marcal, Luiz A. P. [UNESP]; Higuti, Ricardo T. [UNESP]; Kitano, Claudio [UNESP] (Wiley-Blackwell, 2012)
A new and an improved version of the J(1)...J(4) method for optical phase detection, named J(1)-J(3) method, is described, which is more stable to phase drift and simpler for implementation than the original one. The sensor dynamic range is increased while maintaining the accuracy and the minimum detectable phase-shift. The method is experimentally validated by using an electro-optic intensity modulator. The agreement between theoretical and experimental results, based on the 1/f voltage noise, is demonstrated. (C) 2011 Wiley Periodicals, Inc. Microwave Opt Technol Lett, 54:387-392, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.26533
Keywords: interferometry; optical phase measurements; Pockels cell